Pengaruh Promosi Dan Electronic Word Of Mouth(E-Wom) Terhadap Keputusan Pembelian Tiket Bioskop Pada Aplikasi TIX ID (Studi Kasus Pada Prodi Manajemen Universitas Bhayangkara Jakarta Raya) - Indah Sari Ningrum; Yayan Hendayana; Ari Sulistyowati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to measure the influence of promotions and electronic word of mouth (E-wom) on the decision to purchase cinema tickets on the TIX ID application (Case study in the management study program at Bhayangkara University, Jakarta Raya). The sampling technique used in this research was students from Bhayangkara University, Jakarta Raya who had used the TIX ID application. The data collection tool in this research used a questionnaire distributed to 110 respondents. The data analysis method used multiple linear regression analysis. The results of this research partially show that promotions have a significant effect on purchasing decisions and Electronic Word of Mouth (E-WOM) has a significant effect on cinema ticket purchasing decisions on the TIX ID application.